(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The notion of green finance has garnered noteworthy interest in the past several years as a strategy to tackle the urgent environmental issues confronting the international community. This study examines the many facets of sustainable investing and green finance, including their current state, major forces behind them, and future obstacles.The study employs a comprehensive literature review to analyze the existing research and identify the gaps in knowledge. The findings suggest that while awareness of environmental issues is widespread, consumer understanding of green finance remains limited. Furthermore, the paper highlights the opportunities and obstacles associated with the widespread adoption of green finance practices, providing insights for policymakers, financial institutions, and investors.